2021
DOI: 10.1021/acs.biochem.1c00621
|View full text |Cite
|
Sign up to set email alerts
|

The Zinc and Iron Binuclear Transport Center of ZupT, a ZIP Transporter from Escherichia coli

Abstract: ZupT fromEscherichia coliis a member of the Zrt-/Irt-like Protein (ZIP) transporter family, which is responsible for zinc uptake during zinc-sufficient conditions. ZIP transporters have been shown to transport different divalent metal ions including zinc, iron, manganese, and cadmium. In this study, we show that ZupT has an asymmetric binuclear metal center in the transmembrane domain; one metal-binding site, M1, binds zinc, cadmium, and iron, while the other, M2, binds iron only and with higher affinity than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 45 publications
(119 reference statements)
0
6
0
Order By: Relevance
“…Our initial focus was put on the Zn/Cd selectivity because the two metals, both in the IIB column of the periodic table, share similar properties in coordination chemistry. Indeed, the previous studies have indicated that Zn 2+ and Cd 2+ use the same transport pathway through multi-metal ZIPs 32 , 44 , and distinguishing them requires a delicate but less understood mechanism. To precisely measure small kinetic isotope effect of an enzyme, a commonly used approach is the internal competition assay in which a mixture of two competing substrates labeled with light and heavy isotopes respectively is applied to the enzyme for processing 45 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our initial focus was put on the Zn/Cd selectivity because the two metals, both in the IIB column of the periodic table, share similar properties in coordination chemistry. Indeed, the previous studies have indicated that Zn 2+ and Cd 2+ use the same transport pathway through multi-metal ZIPs 32 , 44 , and distinguishing them requires a delicate but less understood mechanism. To precisely measure small kinetic isotope effect of an enzyme, a commonly used approach is the internal competition assay in which a mixture of two competing substrates labeled with light and heavy isotopes respectively is applied to the enzyme for processing 45 .…”
Section: Resultsmentioning
confidence: 99%
“…More importantly, the mutagenesis and functional studies conducted in this work unraveled key molecular determinants of substrate specificity of ZIP8, in particular a conditional selectivity filter. Among the four residues substituted in the 4M variant, only E343 participates in metal binding at the M1 site which is the primary transport site of the ZIPs 6,44,46,57 . Previous multiple sequence analysis has predicted E343 as a key residue involved in determining substrate specificity 14,15 , but its role was evidenced only when the transport dead E343H variant was rescued by the Q180H mutation in the 2M variant (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…ZupT is suspected to transport many divalent cations, as many ZIP family proteins (ZRT, IRT-like Proteins) have been shown to have a broad substrate range (Guerinot, 2000 ). The metal-binding sites of ZupT interacted similarity with zinc and cadmium (Roberts et al., 2021 ), and ZupT was directly shown to enable uptake of cobalt, cadmium, and manganese by E. coli (Grass et al., 2005 ; Taudte & Grass, 2010 ).…”
Section: Resultsmentioning
confidence: 99%
“…While the kinetic studies using the cell-based transport assays suggested a carrier mode for eukaryotic and prokaryotic ZIPs 35 42 , a bacterial ZIP from Bordetella bronchiseptica (ZIPB or BbZIP) reconstituted in proteoliposome was reported to behave like an ion channel 43 . The studies on other bacterial ZIPs reconstituted in proteoliposome, however, showed Michaelis-Menten type kinetics 44 , 45 . Structural studies have provided critical insights into the transport mechanisms for numerous membrane transport proteins.…”
Section: Introductionmentioning
confidence: 98%